PENGARUH STRATEGI PENETAPAN HARGA TERHADAP PENINGKATAN JUMLAH SISWA PADA SMK PGRI BALARAJA (JS (JURNAL SEKOLAH), 2020)
Abstract: The Effect of Pricing Strategies on Increasing the Number of Students at SMK PGRI Balaraja. The method used was explanatory research with a sample of 5 years of education costs incurred by schools and the number of students. The analysis technique uses statistical analysis with regression testing, correlation, determination and hypothesis testing. The results of this study variable pricing strategy obtained a minimum value of Rp. 2,630,000 and a maximum value of Rp. 3,240,000 with an average of Rp. 2,869,000 with a standard deviation of 2,892.74. Variable Increasing the number of students obtained a minimum number of 865 students and a maximum number of 896 students with an average of 877 students with a standard deviation of 12,062. Pricing strategies have a positive and significant effect on increasing the number of students with a regression equation value of Y = 780,401 + 3,367X, and a correlation coefficient of 0.807 or having a very strong level of correlation with a determination value of 65.2%. Hypothesis testing obtained significance of 0,000